COMPLIANCE OF ANTHRAX RECOMBINANT VACCINE PROTOTYPE WITH THE REQUIREMENTS TO IMMUNE-BIOLOGICAL PREPARATIONS - N. I. Mikshis (Sankt-Peterburg : NIIÈM imeni Pastera, 2018)
Current areal of anthrax among live stock and wild animals covers almost all the continents. The cause of human infection is conventionally considered to be the contact with diseased animals in the process of carrying for an animal, forced slaughter or further trimming of carcasses, as well as contact with infected raw materials of animal origin. Licensed vaccines has made an invaluable contribution to the improvement of epidemiological situation on anthrax, however, development of the vaccines complying with current scientific progress remains relevant. We have constructed a vaccine prototype containing recombinant protective antigen and S-layer EA1 protein and added state-of-the-art CpG 2006 adjuvant to the formulation. We have demonstrated the advantage of the lyophilized form of the preparation. Objective — obtainment of anthrax vaccine prototype in lyophilized state and assessment of the prototype compliance with the requirements to vaccine preparations. Materials and methods. Isolation of rPA and EA1 protein was carried out using producer-strain B. anthracis 55ΔTПА-1Spo– on an integrated end-to-end manufacturing line, including concentration, diafiltration and two-phase chromatography. CpG 2006 adjuvant was synthesized according to known sequences. Components were mixed and lyophilized in sublimation unit. Combination of 1% sucrose and 3% glycine was used as cryoprotector. Effectiveness and safety of the preparation were evaluated on the model of BALB/c mice and guinea pigs applying immunological, morphometric, and histological assays. Antibody titers in sera of immunized animals were evaluated using standard ELISA procedures. Protective properties were investigated through LD50 values for the test-strain used on immunized and control animals and immunity index. Results. We have performed complex investigation of the anthrax vaccine prototype, containing B. anthracis 55ΔTПА-1Spo– proteins as main and supplementary antigens, as well as CpG 2006 adjuvant, stabilizers and preservative agent. The prototype meets the requirements to immunobiological medicinal drugs by all physical-chemical properties. Our preparation does not have a toxic effect on the organism of laboratory animals in case of subcutaneous and intraperitoneal administration of single human dose. Pathomorphological study of guinea pigs’ organs immunized with double dose of the vaccine prototype has not revealed any evidence of damaging effect on the cells and tissues of macroorganism. The prototype protects BALB/c mice from the infection with B. anthracis 71/12 test-strain.